Synthesis and Structural and Magnetic Properties of Polycrystalline GaMo4Se8 - José F. Malta; Marta S. C. Henriques; José A. Paixão; António P. Gonçalves (Magnetochemistry, 2023)
GaMo4Se8, is a lacunar spinel where skyrmions have been recently reported. This compound belongs to the Ga<semantics>M4X8</semantics> family, where M is a transition metal (V or Mo) and X is a chalcogenide (S or Se). In this work, we have obtained pure GaMo4Se8 in polycrystalline form through an innovative two-step synthetic route. Phase purity and chemical composition were confirmed through the Rietveld refinement of the powder XRD pattern, the sample characterisation having been complemented with SEM analysis. The magnetic phase diagram was investigated using DC (VSM) and AC magnetometry, which disclosed the presence of cycloidal, skyrmionic and ferromagnetic phases in polycrystalline GaMo4Se8.